Semiotic Analysis of Da'wah Message About Morals in The Short Film Ji Dullah - Imani, Ahmad Yazid (Ath Thariq Jurnal Dakwah dan Komunikasi, 2024)
This research is motivated by the social criticism conveyed in the short film "Ji Dullah," directed by Alif Septian Raksono Putra from EmpatBelas_Project. The research analyzes scenes in the film containing da'wah messages about Islamic ethics (akhlak). The study employs a qualitative method with a descriptive approach. This approach involves analyzing dialogue, scenes, and audio-visual effects to understand the da'wah messages conveyed. Roland Barthes' Semiotic Analysis theory is used as the framework to identify symbols or signs that carry moral or da'wah messages. The data for this research comes from analyzing the film's scenes and descriptions of da'wah messages. Key findings include prohibiting several undesirable traits: arrogance (riya’), succumbing to lust, harsh speech, unjust leader, and bribery. These findings highlight undesirable traits for Muslims as depicted in the film's da'wah messages. Ultimately, the research aims to inspire viewers to cultivate good character and avoid morally wrong actions.